RETRACTED: The Two-Component System CpxRA Negatively Regulates the Locus of Enterocyte Effacement of Enterohemorrhagic Escherichia coli Involving σ32 and Lon protease - De la Cruz, Miguel A.; Morgan, Jason K.; Ares, Miguel A.; Yáñez-Santos, Jorge A.; Riordan, James T.; Girón, Jorge A. (Frontiers in Cellular and Infection Microbiology, 2016)
Enterohemorrhagic Escherichia coli (EHEC) is a significant cause of serious human gastrointestinal disease worldwide. EHEC strains contain a pathogenicity island called the locus of enterocyte effacement (LEE), which encodes virulence factors responsible for damaging the gut mucosa. The Cpx envelope stress response of E. coli is controlled by a two-component system consisting of a sensor histidine kinase (CpxA) and a cytoplasmic response regulator (CpxR). In this study, we investigated the role of CpxRA in the expression of LEE-encoded virulence factors of EHEC. We found that a mutation in cpxA significantly affected adherence of EHEC to human epithelial cells. Analysis of this mutant revealed the presence of high levels of CpxR which repressed transcription of grlA and ler, the main positive virulence regulators of the LEE, and influenced negatively the production of the type 3 secretion system–associated EspABD translocator proteins. It is known that CpxR activates rpoH (Sigma factor 32), which in turns activates transcription of the lon protease gene. We found that transcription levels of ler and grlA were significantly increased in the lon and cpxA lon mutants suggesting that lon is involved in down-regulating LEE genes. In addition, the Galleria mellonella model of infection was used to analyze the effect of the loss of the cpx and lon genes in EHEC’s ability to kill the larvae. We found that the cpxA mutant was significantly deficient at killing the larvae however, the cpxA lon mutant which overexpresses LEE genes in vitro, was unable to kill the larvae, suggesting that virulence in the G. mellonella model is T3SS independent and that CpxA modulates virulence through a yet unknown EHEC-specific factor. Our data provides new insights and broadens our scope into the complex regulatory network of the LEE in which the CpxA sensor kinase plays an important role in a cascade involving both global and virulence regulators.